(untitled) (Bangladesh Journal of Medicine, 2023)
Typhoid fever is an infection caused by Salmonella typhi. The common complications are intestinal perforation and typhoid encephalopathy. Cases of typhoid fever with sepsis and/or disseminated intravascular coagulation (DIC) are rarely reported. A 20 yr old male presented with grade fever, vomiting, diarrhoea.His Dengue NS1 was negative, procalcitonin was high,coagulation profile was altered and developed subclinical DIC along with septicemia within a short period of time which is very rare. Sepsis and DIC are rare complications of typhoid fever. Typhoid fever can be presented with profound bleeding manifestation other than gastrointestinal bleeding, since it is a common symptom of typhoid fever. Further research should be conducted to postulate association between typhoid fever and DIC. Here we reported an unusual case of sepsis which a caused by case of typhoid fever. Bangladesh J Medicine 2023; 34(3): 252-254